Fatty Acid Profile, Total Phenolic Content, and Antioxidant Activity of Niger Seed (Guizotia abyssinica) and Linseed (Linum usitatissimum) - Deme, Tesfaye; Haki, Gulelat D.; Retta, Nigussie; Woldegiorgis, Ashagrie; Geleta, Mulatu (Frontiers in Nutrition, 2021)
Fatty acid composition and antioxidant content are major determinant of vegetable oil quality. Antioxidants are important food components, and there is an increasing interest of replacing synthetic antioxidants with those from natural sources for food industry. The objective of this study was to evaluate fatty acid composition, total phenolic, carotenoid and chlorophyll contents, and antioxidant capacity of different varieties of two oilseed crops. Five niger seed and eight linseed varieties were used. For the analysis of fatty acid composition of the seed oil, gas chromatography method was used. Standard methods were used for total phenolic, carotenoid and chlorophyll contents and antioxidant properties. In niger seed oil, linoleic acid (C18:2) was the dominant fatty acid, accounting for 73.3% (variety Esete) to 76.8% (variety Ginchi) of the total fatty acids. In linseed oil, linolenic acid (C18:3) was the dominant fatty acid accounting for 55.7 (variety Chilalo) to 60.1 (variety Belaye-96). The total phenolic content ranged from 22.4 mg GAE/g (variety Esete) to 27.9 mg GAE/g (variety Ginchi) in niger seed and from 20.5 mg GAE/g (variety Belay-96) to 25.4 mg GAE/g (variety Ci-1525) in linseed. In niger seed, variety Fogera had the highest values for FRAP and radical scavenging activity. The carotenoid content also showed significant variation among the varieties ranging from 2.57 (Esete) to 8.08 (Kuyu) µmol/g for niger and 4.13 (Tole) to 8.66 (Belay-96) µmol/g for linseed. The FRAP assay showed that variety Fogera of niger seed and variety Chilalo of linseed came on top among their respective varieties with values of 57.2 and 30.6, respectively. Both niger seed and linseed were shown to be rich in bioactive compounds. However, significant variation was observed among the varieties of each crop and among the two crops in their total phenolic and carotenoid contents as well as ferric reducing potential and radical scavenging capacity. Principal component analysis revealed the presence of more than one group in both niger seed and linseed. Hence, genetic variation among the varieties should be utilized for improving their desirable characteristics through breeding. Both oil crops can be used as the source of antioxidants for replacing synthetic compounds.